Generation of Photonic Hooks from Patchy Microcylinders - Fen Tang (MDPI AG, 2021)
The photonic hook (PH) is a new type of curved light beam, which has promising applications in various fields such as nanoparticle manipulation, super-resolution imaging, and so forth. Herein, we proposed a new approach of utilizing patchy microcylinders for the generation of PHs. Numerical simulation based on the finite-difference time-domain method was used to investigate the field distribution characteristics of the PHs. By rotating the patchy microcylinder, PHs with different curvatures can be effectively generated, and the PH with a bending angle of 28.4<semantics>∘</semantics> and a full-width-half-maximum of 0.36 <semantics>λ</semantics> can be obtained from 1 <semantics>μ</semantics>m-diameter patchy microcylinders.